Pediatric-adult split liver transplantation: an ethical imperative and systems-based roadmap for global expansion - Long, Tran Cong Duy; Chau, Huynh Tran Bao; Le, Dat Tien; Minh, Thi Tran Nguyen; Minh, Bui Cong; Diep, Anh Le Thien; Van, Hoang Bao Tran; Huynh, Truc Thi Thu; Huy, Nguyen Tien (Frontiers in Transplantation, 2026)
This paradox emphasizes the urgent need to re-engineer transplant systems around pediatric-adult split liver transplantation (SLT). Despite being as effective as whole-liver transplants, SLT remains underutilized due to logistical and policy barriers. We believe that expanding SLT is not only clinically acceptable but a just and effective moral necessity. We propose a five-point action plan, including centralized splitting hubs, NMP-enabled transport, and global pilot programs, to transform SLT from an exception into standard practice.